Making technology work applications in energy and the environment - Deutch, John M. 1938- (Cambridge University Press, 2004)
This book presents fifteen cases of technology applications in the energy and environment sectors, including solar, wind, fuel cell, nuclear, coal combustion and emission control technologies. The case studies demonstrate the importance of an interdisciplinary approach, integrating technical and non-technical aspects of the problem. They also introduce a toolbox of analytical techniques useful in the context of realistic technology application. These techniques include energy and mass balances, project financial analysis tools, treatment of external costs and benefits, probabilistic risk assessment, learning curves, regression analysis, and life cycle costing. Each case study presents a description of the relevant technology at a level accessible to anyone familiar with elementary concepts in basic science and engineering. The book is addressed to upper-level undergraduate students in the natural sciences, engineering and the social sciences who are interested in learning about problems of technology application, as well as technology practitioners in industry and government.